2021
DOI: 10.2478/cee-2021-0063
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Concrete with Recycled Plastic Waste

Abstract: Plastics are a vast group of synthetic or semi-synthetic materials that are often made of polymers. Because of their plasticity, plastics can be molded, extruded, and pressed into solid objects of different sizes. Its extensive use is due to its flexibility, as well as a number of other properties such as light weight, durability, and low manufacturing costs. The high use of plastics has resulted in an increase in solid waste, with domestic waste accounting for a significant portion of it. Since this waste is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It is an approach that has been widely used around the world in the last twenty years. On a global scale, concrete is a commonly used building material in civil engineering structures [7,15,[51][52][53][54][55]. Its use is increasing with the expansion of construction projects because of growing populations [44,[56][57][58][59].…”
Section: Recycled Aggregate Concrete (Rac)mentioning
confidence: 99%
“…It is an approach that has been widely used around the world in the last twenty years. On a global scale, concrete is a commonly used building material in civil engineering structures [7,15,[51][52][53][54][55]. Its use is increasing with the expansion of construction projects because of growing populations [44,[56][57][58][59].…”
Section: Recycled Aggregate Concrete (Rac)mentioning
confidence: 99%
“…However, the use of PET (Polyethylene terephthalate) wastes in concrete could be viable solution to develop lightweight concrete. Reducing the weight of concrete is one of the goals of structures designed to resistant earthquakes (Ahmed, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, demolition waste is increasing and has become one of the most serious concerns worldwide [1][2][3]. So, recycling waste materials in constructions offers environmental as well as economic benefits such as reducing extraction of virgin materials and overall projects costs [2,[4][5][6].Since concrete is the most common construction material and about 75 % of concrete volume is occupied by aggregate, waste materials like crushed concrete and/or crushed bricks have successfully used as coarse and/or fine aggregate in various percentages to produce new concretes even though they, generally; give lower strength and stiffness than conventional concrete [7][8][9][10][11][12]. However, studies show that less or no negative effect is observed when the ratio of waste aggregate is about 50 % or less [1,8,13].…”
mentioning
confidence: 99%
“…On the other hand, demolition waste is increasing and has become one of the most serious concerns worldwide [1][2][3]. So, recycling waste materials in constructions offers environmental as well as economic benefits such as reducing extraction of virgin materials and overall projects costs [2,[4][5][6].…”
mentioning
confidence: 99%